Pengaruh Modal Intelektual dan Struktur Modal terhadap Kinerja Keuangan Pada Bank pembangunan Daerah Bali - Melianti, Ni Kadek; Cipta, Wayan (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effect of: (1) intellectual capital and capital structure on financial performance, (2) intellectual capital on financial performance, (3) capital structure on financial performance. This research design is causal quantitative. The subject used is the Regional Development Bank of Bali and the object of research is intellectual capital, capital structure, and financial performance. Data were collected by recording documents, which were then analyzed by multiple linear regression analysis. The results showed that: (1) intellectual capital and capital structure had an effect on financial performance, (2) intellectual capital had a significant positive effect on financial performance, while (3) capital structure had no effect on financial performance at Bank Pembangunan Daerah Bali